FDR Dan NPF Terhadap ROA dalam Lanskap Perbankan Syariah: Analisis Empiris Bank Syariah Indonesia - Slamet Heri Winarno; Lela Elvira; Mahmud Syarif; Dewi Hudiyah (LPPM Universitas Bina Sarana Informatika, 2025)
This research explores the influence of the Financing to Deposit Ratio (FDR) and Non-Performing Financing (NPF) on Return on Assets (ROA) at Bank Syariah Indonesia over the 2021-2024 period. The study adopts the Partial Least Squares-Structural Equation Modelling (PLS-SEM) approach, which is suitable for analyzing latent variables simultaneously, even when the sample size is relatively small and the data distribution deviates from normality. Data were obtained from Bank Syariah Indonesia’s quarterly financial statements, sourced from the Financial Services Authority (OJK) and the bank’s annual reports. The empirical findings indicate that FDR has a positive but statistically insignificant effect on ROA, while NPF exerts a significant negative influence on ROA. The structural model demonstrates an R² value of 0.745, suggesting that 74.5% of the variation in ROA is explained by the two independent variables. Additionally, the model’s Goodness of Fit index reaches 0.928, indicating strong predictive relevance and model robustness. These results highlight the critical role of managing financing risk and optimizing intermediary functions to enhance the profitability of Islamic banking institutions. The study contributes to the growing body of literature on Islamic finance performance and offers practical insights for policymakers and financial managers in improving asset efficiency through better risk control and strategic financial intermediation.